Experimental assessment of domestic biogas production from organic waste through anaerobic digestion in Chad - Abdelhamid Issa Hassane; Bill Vaneck Bôt; Fatimé Nadji Gisele; Doussi Howe Olivier; Ruben Mouangue (Journal of Emerging Science and Engineering, 2026)
Environmental degradation and health concerns. In this context, the valorisation of organic waste through anaerobic digestion represents a promising alternative for sustainable household energy production. This study presents an experimental assessment of domestic biogas production from organic waste under local conditions in Chad. A pilot-scale anaerobic digestion system was designed and operated for a period of 30 days. The digester was fed with a mixture of vegetable organic waste and fresh cow dung used as inoculum. Key operational parameters, including temperature and pH, were regularly monitored throughout the digestion process. The system was designed to meet the cooking energy needs of a household of eight persons, and the technical feasibility of biogas production was evaluated. The experimental results showed that biogas production started from the tenth day of fermentation and increased progressively with the hydraulic retention time. The pH remained within a range favourable to methanogenic activity, while temperature variations were compatible with mesophilic digestion conditions. The observed biogas production confirmed the methanogenic potential of the selected organic substrates and demonstrated the suitability of the proposed low-cost digester for domestic energy applications. Biogas volume increases with daily feeding (1/60 of the useful volume) and a retention time of 30 days, reaching a maximum volume of 1,2 m³. This can reduce daily consumption by approximately 0,2 m³ of butane, 1,24 kg of charcoal, and 2,5 kg of firewood.The findings indicate that anaerobic digestion of household organic waste can contribute to sustainable energy supply, waste management improvement and reduction of pressure on forest resources in Chad. This study provides practical evidence supporting the deployment of small-scale biogas systems in similar socio-economic contexts.